Immobilized nanoscale zero-valent iron for synergistic enhanced removal of pentachlorobenzene with Pseudomonas sp. JS100 - Ma, Anzhou; Ma, Jianpeng; Chen, Xianke; Zhuang, Guoqiang (Frontiers in Bioengineering and Biotechnology, 2022)
Highly chlorinated benzenes usually have a low efficient degradation in environment. Here we proposed a synergistic removal strategy of pentachlorobenzene (PeCB) using Pseudomonas sp. JS100 coupled with immobilized nanoscale zero-valent iron (NZVI). The structural and textural features of the synergistic system were characterized by X-ray powder diffraction, field emission scanning electron microscopy, and a specific surface area and pore size analysis. Nanoscale zero-valent iron particles were dispersed and attached to the biofilter, which increased the specific surface area to 34.5 m2·g−1. The batch experiment revealed that the removal efficiency of PeCB reached 80.2% in the synergistic system within 48 h. The degradation followed pseudo-first-order reaction kinetics, and the reaction rate constant was measured to be 0.0336 h−1. In the degradation mechanism, PeCB was degraded by NZVI to lower chlorobenzenes, which were utilized by Pseudomonas sp. JS100 as nutrients, thereby achieving rapid removal of PeCB.